PENYULUHAN DAUN KELOR TERHADAP PENINGKATAN PENGETAHUAN ANEMIA PADA IBU HAMIL DI DESA TANAKARAENG KECAMATAN MANUJU - Rahayu Eryanti Kusniyanto; Jumrah Sudirman; Marlina Aziz (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Anemia in pregnant women can increase maternal and child mortality and morbidity rates. Anemia increases the risk of abortion, KJDR, premature birth, hemorrhagic and so on. Anemia in pregnancy affects the growth and development of the fetus both before and after birth. The prevalence of anemia in pregnant women in Indonesia is 48.9%. One of the ways to reduce the incidence of anemia in pregnant women is to provide nutrition education that can help reduce anemia to the community, especially pregnant women. Tanakaraeng Village is used as a counseling location. The method used in this community service activity is lectures and discussions using powerpoint, LCD. From the results of data processing using a paired T test with a sample of 21 people, it was obtained that there was an increase in knowledge from the average value of the pre-test questionnaire, which obtained a value of 45.23 and post-test: 74.76. The result of the paired T test is 0.000. There is an average knowledge before being given counseling and after being given counseling.